Autohydrogenotrophic denitrification by a bioelectrochemical process: A viability study - Mahdi Safari; Abbas Rezaee; Bita Ayati; Ahmad Jonidi Jafari (Iranian Journal of Health, Safety and Environment, 2014)
ABSTRACT In this study, viability of the autotrophic bacteria was investigated in a denitrification process. Bench-scale bioelectrochemical denitrification with separated chambers reactor were applied for nitrate reduction from synthetic wastewater. The influences of current density, retention time, mixing on viability of autotrophic denitrifying bacteria were investigated in the bioelectrochemical reactor (BER). It was found that by increasing the current density up to 8 mA/cm2, nitrate reduction rate was increased. At higher current density (24 - 32 mA/cm2), denitrification rate due to excess of hydrogen gas on cathode surface and accumulation of nitrite, was decreased. Low current density (<16 mA/cm2) has not had a significant effect on viability of denitrifying bacteria. Mixing of the solution reduced the adverse effects of electric current on bacteria and enhanced the denitrification rate which was mainly due to prevention of bacteria localization, increasing the contact of hydrogen and bacteria, and delay in membrane fouling. The viability of cultivable bacteria has not been significantly influenced by running time.